Cabin Assembly Balancing Line on Welding Using Ranked Positional Weight Method - Suryani, Neneng; ETP, Lussiana (ELKHA : Jurnal Teknik Elektro, 2023)
The Indonesian automotive industry has become an essential pillar in the country's manufacturing sector. As production capacity increases, problems will also increase, including disparities in the level of efficiency and productivity of each sub-sector of the manufacturing industry in Indonesia. This problem occurs due to the need for a good process path, such as the uneven distribution of work tasks machines in the work process so that it is possible to harm the company, so a solution is needed to increase the efficiency of the production line. This research aims to improve production efficiency, particularly concerning the use of electricity costs and operator wages on the cabin type S L assembly line, by applying the Ranked Positional Weight (RPW) method. The research phases include data collection, analysis, processing, and evaluation. Based on the SL-type cabin calculations using the RPW method, the track efficiency improved by 4.69% from the initial conditions, while the track effectiveness increased by 75.02% to 79.71%. Increased the production line efficiency has impacted on the decrease in production costs Rp. 13,827,249/month.